The Effects Of Communication Strategies On Intermediate Iranian EFL Learners' Willingness To Communicate - Samian, Hosein Vafadar (2018)
It is too frequently observed that students in EFL classes although motivated to learn a language remain silent and do not initiate or engage in communication when they are free to do so. Due to the importance of communication and language use in language acquisition in the past decade, willingness to communicate (WTC) as the construct to call such ambivalence to account is considered an essential concept in language learning and teaching. Adopting mixed methods design, the present quasiexperimental study investigated the differential effects of communication strategies (CSs) on Intermediate Iranian EFL students' WTC based on participants’ amount of speaking time on allocated discussion topics and number of speaking turns while minimizing the teachers’ immediacy behaviors effects.